The Effect of Project Based Learning Model on Creative Thinking Ability in Biology Learning - Putri Cahaya Illahi; Rahmadhani Fitri; Fitri Arsih (Journal of Digital Learning and Education, 2022)
This research aims to gain insights into the influence of the Project-based learning model on the enhancement of creative thinking skills among high school students in the subject of biology. The low creative thinking skills of high school students and the teacher-centered learning model, which typically involves lectures, have prompted the need for a more active learning process that involves students in the learning process. The Project-based learning model has been identified as a suitable approach for this purpose. To conduct the research, an expost facto method was employed, involving a review of relevant literature on the topic. The findings of the study indicate that the Project-based learning model has a positive impact on the creative thinking skills of high school students, as evidenced by an increase in the average scores of the students. This research adds to the body of knowledge on effective learning methods and has practical implications for educators seeking to enhance the creative thinking skills of their students. Further research could be conducted to explore the potential of the Project-based learning model in other subjects and at different educational levels. Additionally, it would be valuable to examine the long-term effects of the Project-based learning model on the creative thinking skills of students, as well as its potential to foster other desirable outcomes such as critical thinking and problem-solving skills.